The electronic executive instrument in the Saudi system: A comparative study with the German payment order mechanism (Mahnverfahren) - Jumanah Khalid Ahmed Al-Ghamdi; Al-Hanouf Abdulaziz Al-Sulami (International Journal of Law Research and Studies, 2025)
This paper examines the electronic enforceable instrument in the Saudi legal system as a key manifestation of digital transformation in enforcement proceedings. It analyzes its concept, legal nature, and statutory basis, while also exploring its practical application and the legal consequences arising from its enforcement. The study adopts a comparative analytical approach by examining the enforcement of electronic enforceable instruments in Saudi Arabia alongside the German order for payment procedure (Mahnverfahren), as a distinct procedural model for debt collection. The paper aims to assess whether the Saudi system achieves an appropriate balance between procedural efficiency and the protection of the debtor’s rights, particularly in light of the direct enforceability of electronic instruments and the immediate effects of enforcement measures prior to judicial review of execution disputes. The study concludes that while the Saudi enforcement framework ensures a high level of efficiency and speed in debt recovery, it provides relatively limited procedural safeguards for the debtor when compared to the German model, which grants the debtor an early and effective right to object before enforcement effects arise. Accordingly, the paper recommends reconsidering the procedural sequencing of enforcement measures related to electronic enforceable instruments in Saudi Arabia, in a manner that strengthens debtor protection without undermining the effectiveness of enforcement mechanisms.